REINTERPRETASI AYAT-AYAT EKOLOGI DALAM AL-QUR’AN: PERUMUSAN RENCANA AKSI BERBASIS KONSERVASI LINGKUNGAN, MASYARAKAT CERDAS BERKEHIDUPAN - Manik, Wagiman (STIT Al-Ittihadiyah Labuhanbatu Utara, 2023)
The environmental crisis is no longer a national problem, but has become a global problem that is occurring today. Seeing the huge impact caused by this crisis, the world at the 2015 UN general assembly included addressing this environmental crisis in the SDGs goals. In the Islamic view, natural damage occurs due to external factors, namely due to human activity. The Qur'an strongly criticizes all damage caused by human actions on earth, such as Q.S Al-A'raf verse 56. On the other hand, in Q.S Hud verse 61, Allah determines humans as caliphs and prosperers on earth. If studied in depth, many verses from the Qur'an provide solutions to deal with the problem of environmental damage. Through qualitative descriptive methods, the author analyzes the verses of the Al-Qur'an. So the author formulates an action plan to overcome the environmental crisis by creating an educational book that is integrated with the Qur’an. This education aims to create a society that is wise towards nature, cares and is able to preserve nature. This society is what the author calls an intelligent living society.